Handling Concurrent Changes in Collaborative Process Model Development: A Change-Pattern Based Approach - Erol, Selim; Neumann, Gustaf (IEEE International Enterprise Distributed Object Computing Conference workshops, 2013)
Business process modeling has gained increasing interest with the advent of business process management systems in organizational contexts. As business processes are subject to frequent change also respective models are complex and under continuous development with multiple modelers being involved. This paper presents an approach to integrate concurrent changes of multiple modelers equivalently into a resulting process model. Through change patterns we capture the semantics of changes and use them for recognizing instances hereof from subsequent model revisions. These change patterns were identified by analyzing a set of recurring changes during model creation, modification, and refactoring. Together with the concept of conflict types change patterns are used as a conceptual means to implement a semi-automated merging mechanism within a collaborative wiki-based modeling environment. This approach is expected to facilitate smooth (incremental and iterative) development of models in highly dynamic modeling environments and is a human-oriented way to conflict resolution in (concurrent) process model development.